Unexpected influence of acrylamide on clouding behavior of PEO-PPO-PEO triblock copolymers in aqueous solution. (March 2023) - Zheng, Chao; Yu, Xiaoyan; Chen, Xiaoyi; Chang, Mingming
Abstract: Poly(ethylene oxide)- b -poly(propylene oxide)- b -poly(ethylene oxide) (PEO-PPO-PEO) and acrylamide are both commercially available and widely used water-soluble substances. There are many situations that PEO-PPO-PEO coexist with acrylamide in industry applications, while little is known about the influence of acrylamide on cloud point of PEO-PPO-PEO aqueous solution. In this work, it reveals a universal solubilization of PEO-PPO-PEO by acrylamide. There is always an increase in cloud point with addition of acrylamide no matter what the molecular structure and concentration of PEO-PPO-PEO is. It is found the solubilization is more pronounced when PEO-PPO-PEO is with lower molecular weight or lower weight fraction of PPO segments. On the other hand, the cloud point of systems at lower concentration is more sensitive to addition of acrylamide. On the contrary, polyacrylamide exhibits an opposite impact on cloud point of PEO-PPO-PEO. Acrylamide/PEO-PPO-PEO solution changes from clear to cloudy after polymerization of acrylamide. Graphical Abstract: Acrylamide induces a universal solubilization of PEO-PPO-PEO aqueous solution, which is affected by molecular structure and concentration. This solubilization is suppressed by polymerization of acrylamide leading to a polymerization-induced clouding phenomenon. ga1